PENGEMBANGAN E-MODUL IPAS TERINTEGRASI STEM PADA MATERI SIKLUS AIR DI KELAS V SEKOLAH DASAR - Desi Marliani Rahmania; Ali Ismail; Rana Gustian Nugraha (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The limited integration of interactive and contextual digital learning materials in Science and Social Studies (IPAS) instruction at the elementary school level remains a considerable obstacle in the implementation of the Merdeka Curriculum. A real-world-oriented learning approach is essential to foster students’ 21st-century competencies. This study aims to develop a STEM-integrated e-module on the water cycle topic for fifth-grade students in elementary schools. The research employed a Research and Development (R&D) methodology using the ADDIE development model, which comprises five stages: Analyze, Design, Develop, Implement, and Evaluate. Data were collected through interviews and questionnaires. The product was validated by five experts, including two media experts and three content experts. The validation results indicated that the e-module achieved an average score of 96,65% from media experts and 94% from content experts, resulting in a combined score of 95,25%, which falls into the “highly valid” category. The practicality of the e-module was assessed through individual trials (n = 3; 100%), small-group trials (n = 24; 87%), and large-group trials (n = 27; 81,75%), with an overall average score of 88.6%, classified as “highly practical.” These findings confirm that the developed STEM-integrated e-module is both valid and practical, and thus appropriate to be implemented as a digital instructional material in IPAS learning on the water cycle topic at the elementary school level.